Antioxidant and Hypocholesterolemic Properties of Functional Soy Yogurts Fortified with ω‐3 and ω‐6 Polyunsaturated Fatty Acids in Balb/c Mice. Issue 5 (19th March 2019) - Sengupta, Samadrita; Koley, Hemanta; Dutta, Shanta; Bhowal, Jayati
Abstract : Increase of ω3 and ω6 polyunsaturated fatty acids (PUFA) intake is currently recommended. Yogurt, which is already popular, offers a functional food matrix to deliver ω3 and ω6 PUFAs. The aim of this study is to investigate the antioxidative and cholesterol‐lowering properties of functional soy yogurts fortified with fish oil (FO) containing eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and Evening primrose oil (EPO) containing gamma linolenic acid (GLA) in diet induced hypercholesterolemic mice. Adding FO and EPO results in a significant reduction in the serum total cholesterol (TC), triglycerides (TG) and low–density lipoprotein cholesterol (LDL‐C), and the atherogenic index of hypercholesterolemic mice when compared with soy yogurt (control) only. Soy yogurts supplemented with functional lipids had significantly improved the high density lipoprotein cholesterol (HDL‐C) in serum, super oxide dismutase and catalase level in liver homogenate and significantly declined the serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and gamma glutamyl transferase activities. Practical Applications : FO and EPO may be considered as novel functional food ingredients for soy yogurt production. The process is commercially economical in view of the uses of seed flour as direct raw material without beany odor problem for making non‐dairy food product. Consumption of poly unsaturated fatty acid fortified soy yogurt results in a significant reduction in the liver total cholesterol of hypercholesterolemic mice when compared with soy yogurt (control) only. Abstract : Consumption of poly unsaturated fatty acid fortified soy yogurt results in a significant reduction in the liver total cholesterol of hypercholesterolemic mice when compared with soy yogurt (control) only.